Legal basis of crop insurance in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article deals with one of the most important elements of the social functions of the state – in crop insurance. The author explores the practice and features of compulsory agricultural insurance in modern Kazakhstan.The basic idea, voiced in an article – inadequate organization of agriculture, as the most important sector of the economy.Agriculture – it is the exclusive sector of the economy that has been, is and will remain the main type of human activities, irrespective of the rapid development of urbanization, industries and innovative technologies. In general, there is objective evidence that the agricultural sector in Kazakhstan will be a harbinger of economic growth. However, in this article the actual problems that are contrary to the dynamic shift in agricultural development – problem selhoztovaroproizvodstva insurance system, ill-conceived policy of state support, the question of the formation of production cooperatives, a lack of qualified specialists and etc.Key words: agriculture, insurance, agricultural production, agricultural insurance, agriculture, compulsory insurance, agri-food market, agriculture, food products.